Effectiveness of elephant grass roots in improving soil shear strength for slope reinforcement - Munirwan, Reza Pahlevi; Syarifah, Milasafarah; Sungkar, Munira; Gunawan, Hendra; Putra Jaya, Ramadhansyah; Aizat, Mohd Taib @ Taib; Yuliana, Yuliana; Kamchoom, Viroon (Elsevier B.V., 2025)
Slope instability and landslides remain major geotechnical concerns in tropical regions, where intense rainfall, high humidity, and extensive human activities such as deforestation and poor land management accelerate erosion and ground failure. As a sustainable alternative to conventional engineering solutions, vegetation-based methods have gained increasing attention, particularly for their ability to reinforce soil through root systems. This study investigates the potential of elephant grass (Pennisetum purpureum) roots to enhance the shear strength of tropical soils for slope stabilization. Soil samples categorized as silty sand, clayey sand, and clay were collected and subjected to laboratory testing. Roots were added at varying proportions (0.1 %, 0.3 %, and 0.5 %) and lengths (2 cm and 3 cm), and samples were tested using direct shear tests to determine their mechanical behavior. Root tensile strength was also evaluated to assess its contribution to soil reinforcement. Additionally, scanning electron microscopy (SEM) was used to examine the microstructural interactions between roots and soil particles. The results revealed significant improvements in cohesion and internal friction angles, with optimal reinforcement observed at 0.3 % root content and 3 cm root length, especially in clay (cohesion = 0.61 kg/cm2, friction angle = 12.56°) and clayey sand (cohesion = 0.76 kg/cm2, friction angle = 13.29°). SEM analysis confirmed effective physical bonding and interlocking between roots and soil matrices. These findings show that elephant grass roots are an effective, eco-friendly solution for stabilizing landslide-prone soils, supporting bioengineering research and guiding future field validation and long-term performance studies.